Farmers' perceptions of erosion by wind and water in northern Burkina Faso - Visser, S. M.; Leenders, J. K.; Leeuwis, M. (Land degradation & development, 2003)
Wind and water erosion are widespread phenomena throughout the Sahel, especially in the early rainy season, when high‐intensity rainstorms are often preceded by severe windstorms. This paper describes the results of a survey on the farmers' perceptions of wind and water erosion processes and control measures. In three villages in northern Burkina Faso, 60 farmers were interviewed using semi‐structured questionnaires. According to most of the farmers, wind‐blown particle transport has an influence on the fertility and the infiltration capacity of the soils. They considered wind‐blown particle transport damaging for their crops. Seedlings are damaged by scouring grains of sand or lost when buried in sand deposits. Only 32 per cent of the farmers observed runoff and 15 per cent observed erosion and deposition during periods of high intense rainfall. According to 22 per cent of the farmers intense rainfall has a negative effect on crop production. Plants die because of the effects of stagnating water and plants are damaged by the forces of flowing water. All farmers are familiar with techniques to reduce soil erosion and 96 per cent applied one or more of these techniques. The indigenous techniques are application of manure and mulch. The main constraints to apply these techniques are lack of labour, manure and mulch. New techniques introduced by agricultural organizations are zaï (a traditional agricultural practice whereby pits of diameter 10–15 cm are filled with compost for sowing) and half‐lines, stone rows and sand ridges. Farmers have a good knowledge of wind erosion processes, but do not report the effects of water erosion processes. The farmers are willing to apply new techniques to control soil erosion, but the main constraints to apply these measures are insufficient knowledge and lack of labour. Copyright © 2002 John Wiley & Sons, Ltd.